Clinical features, outcome, and illness severity scoring in 32 dogs with urosepsis (2017–2018). Issue 2 (3rd November 2021) - Perry, Kayla M.; Lynch, Alex M.; Caudill, Alexander; Vigani, Alessio; Roberston, James B.; Vaden, Shelly
Abstract: Objective: To describe the clinical features, outcome, and utility of illness severity scoring in dogs diagnosed with urosepsis. Design: Retrospective study (2017–2018). Setting: University teaching hospital. Animals: Thirty‐two dogs diagnosed with urosepsis secondary to pyometra, prostatitis, or pyelonephritis. Interventions:  None. Measurements and Main Results: Urosepsis was identified in 32 dogs, consisting of 9 of 32 (28.1%) with pyometra, 7 of 32 (21.8%) with prostatitis, and 16 of 32 (50%) with pyelonephritis. In total, 28 (87.5%) dogs survived to discharge, with the following group‐specific survival rates: pyometra, 9 of 9 (100%); prostatitis, 5 of 7 (71.4%); and pyelonephritis, 14 of 16 (87.5%). Positive bacterial cultures were obtained in 27 of 32 (84.1%) dogs. The most commonly implicated pathogens were Escherichia coli (14/37 [37.8%]), Klebsiella pneumoniae (8/37 [21.6%]), and Staphylococcus pseudintermedius (6/37 [16.2%]). Multiple organ dysfunction syndrome (MODS) was identified in 21 of 32 dogs (65.6%). Although the presence of MODS was not different between survivors and nonsurvivors ( P  = 0.6), nonsurvivors had more dysfunctional organs ( P  = 0.04). Nonsurvivors also had higher Acute Patient Physiology and Laboratory Evaluation (APPLEFAST ) scores compared to survivors ( P  = 0.01). Conclusions: Survival of dogs with urosepsis was good and may be higher than for other sources of sepsis. Compared to survivors, nonsurvivors had more dysfunctional organs and higher illness severity scores, which may be helpful in the assessment and management of dogs with urosepsis.